Analisis Yuridis Sumberdaya Alam dalam Rangka Pembangunan Kawasan Wisata Teluk Kiluan Berbasis Kearifan Lokal - Lintje Anna Marpaung; . Ardiansyah; Rifandy Ritonga (KEADILAN PROGRESIF, 2016)
Kiluan Bay is one of the areas that have great potential of tourism in Tanggamus, Lampung province that offers the beauty of a bay with a variety of marine life. The abundance of this potential to the absence of adequate arrangements bebasis tourism development on local wisdom that regulates the legal basis for the development of tourism and the legal basis Conservation of natural resources in the Gulf Kiluan travel.